Double-carbon-layer-coated silicon-carbon negative electrode material as well as preparation method and application thereof

By adopting double carbon layer cladding technology on silicon carbon negative electrode materials, the problem of electrode structure failure caused by volume expansion of silicon material during charging and discharging is solved, the cyclic stability and electrochemical performance of the material are improved, and high energy density and excellent charging and discharging performance are achieved.

CN119627083APending Publication Date: 2025-03-14JIANGSU TANSHI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411908370.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The theoretical capacity of traditional graphite negative electrode materials is limited. As a substitute material, silicon, as a substitute material, causes the electrode structure to be damaged due to volume expansion during charging and discharging, and its intrinsic conductivity is poor, which limits the performance of capacity and rate performance.

Method used

A double carbon layer is used to coat the silicon carbon negative electrode material, and a loose and porous inner carbon layer and a high-density outer carbon layer are uniformly formed on the surface of the nano-silicon material by spray drying and liquid phase coating to form a composite microparticle structure with double carbon coated silicon particles.

Benefits of technology

It improves the cyclic stability and electrochemical performance of the material, enhances the capacity retention and rate performance, is suitable for industrial production, and significantly improves the energy density and charge and discharge performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627083A_ABST
    Figure CN119627083A_ABST
Patent Text Reader

Abstract

The invention provides a double-carbon-layer-coated silicon-carbon negative electrode material and a preparation method and application thereof.According to the method, a nano silicon material can be preliminarily and uniformly coated with an amorphous carbon precursor material to form an inner carbon layer by means of a spray drying method; the preparation method comprises the following steps: preparing a nanometer silicon material, uniformly coating asphalt by using a liquid phase coating method to form an outer carbon layer so that the surface of the nanometer silicon material is uniformly coated with a double-carbon-layer material, carbonizing the nanometer silicon material coated with the double-carbon-layer material in inert gas by stages, gradually removing volatile substances from the double-carbon-layer material by gradually increasing the carbonization temperature, and preparing the nanometer silicon material with the double-carbon-layer material. And finally, the silicon-carbon negative electrode material with the double-carbon-layer-coated micro-nano spherical structure is obtained, and the double-carbon-layer-coated silicon-carbon negative electrode material shows excellent performance in the aspects of initial capacity, reversible capacity and residual capacity retention rate after circulation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of electrode materials, and in particular to a double-carbon layer coated silicon-carbon negative electrode material, a preparation method thereof, and an application thereof. Background Art

[0002] In recent years, with the development of society and the progress of the times, new energy materials have become increasingly popular, and people's requirements for the new energy industry are also constantly increasing. Lithium-ion batteries, as representatives of secondary batteries, have been widely used, and their traditional graphite anodes can no longer meet the needs of modern society due to the limitation of theoretical capacity (372 mAh / g). Silicon has become an ideal choice for the development of high-energy-density battery anode materials due to its high theoretical capacity (4200 mAh / g), low lithium insertion potential (0.5 V), and sufficient reserves. Although silicon has such a high theoretical capacity, it still faces many problems in practical applications: First, silicon as a negative electrode material is accompanied by severe volume expansion during lithium removal and lithium insertion, resulting in cracking and fragmentation of the electrode material, and falling off from the current collector and losing electrochemical performance. Second, the intrinsic conductivity of silicon is poor, resulting in slow electrochemical kinetics, which limits the performance of the capacity and rate performance of silicon negative electrode materials.

[0003] At present, the commonly used strategies for improving silicon-based negative electrodes mainly include silicon nano-ization, porosity, and silicon-carbon composites. Among them, silicon-carbon materials have received extensive attention and research due to their good conductivity, low volume expansion, and good compatibility between silicon and carbon. However, there are still some problems with the current preparation method. When silicon is directly mixed with carbon materials to prepare silicon-carbon composite materials, the resulting material has certain restrictions on the silicon content. When the silicon content is too high, the volume expansion is still obvious, resulting in damage to the electrode structure, thereby affecting the performance and life of the battery. In addition, when various forms of carbon coating are performed on the silicon surface, if the carbon coating is too thick or uneven, the internal resistance of the electrode may increase and the charge and discharge performance of the battery may be reduced. During long-term charge and discharge cycles, the carbon coating may also be damaged or peeled off, causing the silicon surface to be exposed to the electrolyte, which in turn causes a series of problems such as capacity decay.

[0004] To solve the above problems, it is crucial to choose a suitable coating material and coating method. Therefore, it is necessary to develop a method that can uniformly coat the surface of the silicon material with a carbon layer and avoid the cracking of the prepared silicon-carbon material due to volume expansion during the charging and discharging process. Summary of the invention

[0005] The purpose of the present application is to provide a double carbon layer coated silicon carbon negative electrode material, its preparation method and application. The double carbon layer coated silicon carbon negative electrode material has a loose and porous middle carbon layer and a high-density outer carbon layer, forming a composite micron particle structure of double-layer carbon-coated silicon particles, and at the same time has a higher specific capacity and good cycle performance, and shows superior performance in terms of initial capacity, reversible capacity and residual capacity retention rate after cycling.

[0006] In a first aspect, the present application provides a method for preparing a double carbon layer coated silicon-carbon negative electrode material, characterized in that it comprises: (1) Solution preparation: dispersing the nano-silicon material in water, adding the amorphous carbon precursor material to dissolve and mix and disperse to obtain a precursor solution, wherein the mass ratio of the nano-silicon material to the amorphous carbon precursor material is 1:(0.5-4); (2) spray drying: spray drying the precursor solution to obtain primary particles; (3) Liquid phase coating: dissolving the primary particles and asphalt in a solvent, mixing and stirring, and heating and evaporating to obtain a silicon-carbon precursor coated with a double carbon layer; (4) Carbonization: The silicon-carbon precursor is heated to 300-400°C in an inert atmosphere for low-temperature carbonization for 1-2 h, and then heated to 800-100°C for high-temperature carbonization and heat preservation for 1-2 h. After cooling, the double carbon layer-coated silicon-carbon negative electrode material is obtained.

[0007] The preparation method of the double carbon layer coated silicon-carbon negative electrode material provided by the present invention is as follows: firstly, the nano silicon material and the amorphous carbon precursor material are dissolved in water, and after being evenly dispersed, the mass ratio of the nano silicon material to the amorphous carbon precursor material is controlled, and the amorphous carbon precursor material is initially and evenly coated on the nano silicon material by spray drying to obtain primary particles coated with an inner carbon layer, and then the primary particles and asphalt are uniformly mixed in a solvent by liquid phase coating, and the solvent is further evaporated by heating to make the asphalt uniformly coated on the primary particles to form an outer carbon layer. Through the above operation, the surface of the nano silicon material can be uniformly coated with the double carbon layer material, and further, the nano silicon material coated with the double carbon layer material is carbonized in stages in an inert gas, and the double carbon layer material is gradually removed of volatile substances by gradually increasing the carbonization temperature to form a stable carbon structure, and finally a silicon-carbon negative electrode material with a micro-nano spherical structure coated with a double carbon layer is obtained.

[0008] Based on the requirements of stability and conductive properties of silicon-carbon materials, the present invention designs a loose porous inner carbon layer and a high-density outer carbon layer on the surface of nano-silicon material, and adopts different coating methods and coating materials according to the different properties required of the inner carbon layer and the outer carbon layer, so that under staged carbonization, a composite micron particle structure of double-layer carbon-coated silicon particles is formed.

[0009] Among them, because the first coating only needs to initially wrap the nano-silicon material, and what needs to be prepared is a loose and porous inner carbon layer structure, the spray drying method is used in the first coating, which can complete the transformation from liquid to solid in a short time, and accurately control the particle size and distribution of the obtained powder, better maintain the original form of the raw material, and facilitate the subsequent secondary coating. At the same time, the spray drying equipment is easy to operate and easy to realize automatic control, which is suitable for large-scale production. Further, the primary particles are prepared by the spray drying method. The equipment can granulate while drying, so that appropriate pores are left inside the primary particles, and the pore structure is maintained. This can avoid the phenomenon of cracks in the prepared silicon-carbon material due to volume expansion during the charging and discharging process as much as possible.

[0010] The secondary coating adopts liquid coating to reduce the agglomeration of primary particles during the secondary coating process, improve its dispersibility in the solvent, achieve a uniform and dense coating layer at the nanometer or micrometer scale, and improve the performance of the material. The present invention adopts different coating methods according to the requirements of different carbon layers, and adopts a simple operation method while achieving high performance of the material, so that it is easy to industrialize.

[0011] Furthermore, the present invention utilizes an inner carbon layer with a loose porous structure to better buffer the volume change of silicon particles during the charge and discharge process, reduce internal stress, and thus improve the cycle stability of the material.

[0012] The porous structure of the inner carbon layer also has some defects, such as lower electrical conductivity and thermal conductivity, and its higher specific surface area may cause more interface side reactions, affecting the stability of the material. Therefore, the present invention designs a dense outer carbon layer on the surface of the inner carbon layer to make up for the above defects. During the secondary liquid phase coating, since the asphalt has good fluidity and adhesion when it reaches a certain temperature, it can fill the large pores on the surface of the inner carbon layer during the first coating, thereby modifying the structural defects and making the material structure denser. Therefore, the dense outer carbon layer structure obtained by carbonizing the asphalt helps to form a stable SEI film, improve the thermal stability and electrical conductivity of the material, make up for the shortcomings of the inner carbon layer, and thus improve the performance of the prepared silicon-carbon negative electrode material in all aspects.

[0013] In some embodiments, the amorphous carbon precursor in step (1) includes at least one of glucose, sucrose, water-soluble phenolic resin, starch, and asphalt.

[0014] These amorphous carbon precursors all have a high carbon content and are easy to process, and can be used to form a loose and porous inner carbon layer structure. Among them, when using water-soluble phenolic resin, the water-soluble phenolic resin has a high hardness and mechanical strength after carbonization. The water-soluble phenolic resin is used to coat silicon / graphene once during spray drying to form an inner carbon layer, which can effectively alleviate the volume expansion of silicon while reinforcing the micro-nano spherical structure.

[0015] In some embodiments, the nano-silicon material in step (1) is dispersed by ultrasound, the ultrasonic dispersion time is 0.5-3 hours, and the particle size of the nano-silicon material is 50 nm-500 nm.

[0016] In the embodiment, the nano-silicon material is evenly dispersed in the precursor solution by ultrasonic dispersion, which is beneficial to the uniformity of the subsequent spray drying coating of the inner carbon layer.

[0017] In some embodiments, in step (1), the precursor solution also includes a conductive agent, and the conductive agent includes at least one of exfoliated graphene, graphene oxide, conductive graphite, carbon black, carbon nanotubes, and carbon fibers. The mass ratio of the nano-silicon material to the conductive agent is 1:(0.8-2).

[0018] In the embodiment, adding a conductive agent to the precursor solution can improve the conductivity of the prepared silicon-carbon material and optimize the interface performance. For example, the mechanical properties and flexibility of the exfoliated graphene can be used to strengthen the interface bonding force between silicon and graphene, and the exfoliated graphene and nano-silicon are used as the core to construct a three-dimensional conductive network structure, which not only improves the conductivity of the material, but also evenly disperses the nano-silicon.

[0019] In some embodiments, in step (1), the precursor solution further comprises a binder, and the binder comprises at least one of sodium carboxymethyl cellulose, polyacrylic acid, and polyvinyl pyrrolidone, and the mass ratio of the nano-silicon material to the binder is 1:(0.01-0.2).

[0020] In the embodiment, adding a binder into the precursor solution can make the inner carbon layer and the nano-silicon material more tightly bonded, and the coating of the inner carbon layer is more uniform.

[0021] In some embodiments, in step (2), the air inlet temperature in the spray drying experiment is 140-220°C, and the air outlet temperature is 60-90°C.

[0022] In some embodiments, in step (3), the asphalt includes at least one of natural asphalt, coal tar asphalt, petroleum asphalt or modified asphalt, the mixing time is 0.5-3 h, and the stirring speed is 500-650 rpm.

[0023] In the embodiment, asphalt has excellent adhesion, anti-aging and elasticity, and is an excellent material for the outer carbon layer. At the same time, these asphalts have different advantages, and different materials can be selected according to material requirements.

[0024] In some embodiments, it is characterized in that in the step (4), the silicon-carbon precursor is heated at a heating rate of 5-10°C / min in an argon atmosphere.

[0025] In the embodiment, the carbonization temperature is gradually increased so that the inner and outer carbon layers are carbonized in stages to form an excellent double carbon layer coating structure.

[0026] In a second aspect, the present application provides a double carbon layer coated silicon-carbon negative electrode material, characterized in that the double carbon layer coated silicon-carbon negative electrode material is prepared by the method described in the first aspect.

[0027] In a third aspect, the present application provides a lithium-ion battery, comprising the double-carbon layer-coated silicon-carbon negative electrode material described in the second aspect.

[0028] The beneficial effects of the double carbon layer coated silicon carbon negative electrode material and the preparation method thereof provided in the present application include but are not limited to the following: The silicon-carbon material prepared by the present invention has a loose and porous middle carbon layer and a high-density outer carbon layer, forming a composite micron particle structure of double-layer carbon-coated silicon particles. The porous structure of the inner carbon layer can better buffer the volume changes of silicon particles during the charging and discharging process, reduce internal stress, and thus improve the cyclic stability of the material. The outer carbon layer structure obtained by carbonizing asphalt can fill the larger pores formed by a single coating, further modifying structural defects, making the material structure denser, and helping to form a stable SEI film.

[0029] The double carbon layer silicon-carbon negative electrode material prepared by the present invention has a higher specific capacity, good cycle performance, high capacity retention rate, simple preparation method, simple raw material source, low cost, and is suitable for industrial production.

[0030] The silicon-carbon negative electrode material prepared by the present invention has a high initial coulombic efficiency and capacity retention rate, and shows superior performance in terms of initial capacity, reversible capacity and residual capacity retention rate after cycling compared with a commercial silicon-carbon negative electrode material on the market. Therefore, it has a wide range of application prospects in the field of lithium-ion batteries and can significantly improve the energy density and charge and discharge performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1The SI@EG@PF-1 material prepared in Example 1, the SI@EG@PF-2 material prepared in Example 2, the SI@EG@PF-3 material prepared in Example 3, the SI@EG@PF@C-1 material prepared in Example 4, the SI@EG@PF@C-2 material prepared in Example 5, the SI@EG@PF@C-3 material prepared in Example 6, Comparative Example 1 is an uncoated nano-silicon material, and Comparative Example 2 is a scanning electron microscope image (SEM) of a commercial silicon-carbon material A.

[0032] Figure 2 The SI@EG@PF-1 material prepared in Example 1 was -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0033] Figure 3 The SI@EG@PF-2 material prepared in Example 2 was -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0034] Figure 4 The SI@EG@PF-3 material prepared in Example 3 was -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0035] Figure 5 The SI@EG@PF@C-1 material prepared in Example 4 was -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0036] Figure 6 The SI@EG@PF@C-2 material prepared in Example 5 was -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0037] Figure 7 The SI@EG@PF@C-3 material prepared in Example 6 was -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0038] Figure 8 The uncoated nano-silicon material prepared in Comparative Example 1 is -1 Plot of cyclicity at different current densities.

[0039] Fig. 9 A commercial silicon-carbon material A prepared in Comparative Example 2 at 1 A g -1 Plot of Coulombic efficiency and cycling performance at different current densities.

[0040] Fig.10The SI@EG@PF@C-2 material prepared in Example 5 and a commercial silicon-carbon material A prepared in Comparative Example 2 were compared at 200 mA g -1 Comparison of Coulombic efficiency and cycle performance under different current densities.

[0041] Fig.11 It is a comparison chart of the rate performance of the embodiment and the comparative example at different current densities.

[0042] Fig.12 This is the BET data of Example 2.

[0043] Fig.13 This is the BET data of Example 5. DETAILED DESCRIPTION

[0044] The following description provides specific application scenarios and requirements of the present application, with the purpose of enabling those skilled in the art to make and use the content in the present application. It will be apparent to those skilled in the art that various local modifications to the disclosed embodiments are apparent, and the general principles defined herein may be applied to other embodiments and applications without departing from the spirit and scope of the present application. Therefore, the present application is not limited to the embodiments shown, but to the widest scope consistent with the claims.

[0045] The present application provides a method for preparing a double carbon layer coated silicon-carbon negative electrode material, which is characterized by comprising: (1) Solution preparation: dispersing the nano-silicon material in water, adding the amorphous carbon precursor material to dissolve and mix and disperse to obtain a precursor solution, wherein the mass ratio of the nano-silicon material to the amorphous carbon precursor material is 1:(0.5-4); (2) spray drying: spray drying the precursor solution to obtain primary particles; (3) Liquid phase coating: dissolving the primary particles and asphalt in a solvent, mixing and stirring, and heating and evaporating to obtain a silicon-carbon precursor coated with a double carbon layer; (4) Carbonization: The silicon-carbon precursor is heated to 300-400°C in an inert atmosphere for low-temperature carbonization for 1-2 h, and then heated to 800-100°C for high-temperature carbonization and heat preservation for 1-2 h. After cooling, the double carbon layer-coated silicon-carbon negative electrode material is obtained.

[0046] The preparation method of the double carbon layer coated silicon-carbon negative electrode material provided by the present invention is as follows: firstly, the nano silicon material and the amorphous carbon precursor material are dissolved in water, and after being evenly dispersed, the mass ratio of the nano silicon material to the amorphous carbon precursor material is controlled, and the amorphous carbon precursor material is initially and evenly coated on the nano silicon material by spray drying to obtain primary particles coated with an inner carbon layer, and then the primary particles and asphalt are uniformly mixed in a solvent by liquid phase coating, and the solvent is further evaporated by heating to make the asphalt uniformly coated on the primary particles to form an outer carbon layer. Through the above operation, the surface of the nano silicon material can be uniformly coated with the double carbon layer material, and further, the nano silicon material coated with the double carbon layer material is subjected to staged carbonization with temperature gradient changes in an inert gas, and the double carbon layer material is gradually removed of volatile substances by gradually increasing the carbonization temperature to form a stable carbon structure, and finally a silicon-carbon negative electrode material with a micro-nano spherical structure coated with a double carbon layer is obtained.

[0047] Based on the requirements of stability and conductive properties of silicon-carbon materials, the present invention designs a loose porous inner carbon layer and a high-density outer carbon layer on the surface of nano-silicon material, and adopts different coating methods and coating materials according to the different properties required of the inner carbon layer and the outer carbon layer, so that under staged carbonization, a composite micron particle structure of double-layer carbon-coated silicon particles is formed.

[0048] The electronic-ion mixed conductor sulfide electrolyte material provided in the present application and its preparation method and application will be described in detail below in conjunction with specific embodiments.

[0049] The present application provides a method for preparing a double carbon layer coated silicon-carbon negative electrode material, which is characterized by comprising: (1) Solution preparation: dispersing the nano-silicon material in water, adding the amorphous carbon precursor material to dissolve and mix and disperse to obtain a precursor solution, wherein the mass ratio of the nano-silicon material to the amorphous carbon precursor material in the precursor solution is 1:(0.5-4); for example, 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4; (2) spray drying: spray drying the precursor solution to obtain primary particles; (3) Liquid phase coating: dissolving the primary particles and asphalt in a solvent, mixing and stirring, and heating and evaporating to obtain a silicon-carbon precursor coated with a double carbon layer; (4) Carbonization: The silicon-carbon precursor is heated to 300-400°C in an inert atmosphere for low-temperature carbonization for 1-2 h, and then heated to 800-100°C for high-temperature carbonization and heat preservation for 1-2 h. After cooling, the double carbon layer-coated silicon-carbon negative electrode material is obtained.

[0050] In some embodiments, the amorphous carbon precursor in step (1) includes at least one of glucose, sucrose, water-soluble phenolic resin, starch, and asphalt.

[0051] These amorphous carbon precursors all have a high carbon content and are easy to process, and can be used to form a loose and porous inner carbon layer structure. Among them, when using water-soluble phenolic resin, the water-soluble phenolic resin has a high hardness and mechanical strength after carbonization. The water-soluble phenolic resin is used to coat silicon / graphene once during spray drying to form an inner carbon layer, which can effectively alleviate the volume expansion of silicon while reinforcing the micro-nano spherical structure.

[0052] In some embodiments, the nano-silicon material in step (1) is dispersed by ultrasound, the ultrasonic dispersion time is 0.5-3 hours, and the particle size of the nano-silicon material is 50 nm-500 nm.

[0053] In the embodiment, the nano-silicon material is evenly dispersed in the precursor solution by ultrasonic dispersion, which is beneficial to the uniformity of the subsequent spray drying coating of the inner carbon layer.

[0054] In some embodiments, in step (1), the precursor solution also includes a conductive agent, and the conductive agent includes at least one of exfoliated graphene, graphene oxide, conductive graphite, carbon black, carbon nanotubes, and carbon fibers. The mass ratio of the nano-silicon material to the conductive agent is 1:(0.8-2).

[0055] In the embodiment, adding a conductive agent to the precursor solution can improve the conductivity of the prepared silicon-carbon material and optimize the interface performance. For example, the mechanical properties and flexibility of the exfoliated graphene can be used to strengthen the interface bonding force between silicon and graphene, and the exfoliated graphene and nano-silicon are used as the core to construct a three-dimensional conductive network structure, which not only improves the conductivity of the material, but also evenly disperses the nano-silicon.

[0056] In some embodiments, in step (1), the precursor solution further comprises a binder, and the binder comprises at least one of sodium carboxymethyl cellulose, polyacrylic acid, and polyvinyl pyrrolidone, and the mass ratio of the nano-silicon material to the binder is 1:(0.01-0.2).

[0057] In the embodiment, adding a binder into the precursor solution can make the inner carbon layer and the nano-silicon material more tightly bonded, and the coating of the inner carbon layer is more uniform.

[0058] In some embodiments, in step (2), the air inlet temperature in the spray drying experiment is 140-220°C, for example, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C or 220°C, and the air outlet temperature is 60-90°C, for example, 60°C, 70°C, 80°C or 190°C.

[0059] In some embodiments, in step (3), the asphalt includes at least one of natural asphalt, coal tar asphalt, petroleum asphalt or modified asphalt, the mixing time is 0.5-3 h, and the stirring speed is 500-650 rpm, for example, 500 rpm, 550 rpm, 600 rpm or 650 rpm.

[0060] In the embodiment, asphalt has excellent waterproof performance, corrosion resistance, adhesion, aging resistance, and elasticity, and is an excellent material for the outer carbon layer. At the same time, these types of asphalt have different advantages, and different materials can be selected according to material requirements.

[0061] In some embodiments, it is characterized in that in the step (4), the silicon-carbon precursor is heated at a heating rate of 5-10°C / min in an argon atmosphere.

[0062] In the embodiment, the carbonization temperature is gradually increased so that the inner and outer carbon layers are uniformly carbonized in stages to form an excellent double carbon layer coating structure. Example 1

[0063] 4 g of nano-silicon powder (80 nm) was dispersed in 150 mL of deionized water to obtain dispersion 1, and the dispersion was ultrasonically dispersed for 1 h. 3.2 g of graphene was dispersed in 100 mL of deionized water to obtain dispersion 2, and then stirred. 1.44 g of glucose, 0.72 g of cmc and 2.67 g of water-soluble phenolic resin (solid content of 70%) were dissolved in 150 mL of deionized water and stirred to obtain solution 3. After the above dispersion 2 and solution 3 were poured into dispersion 1, the mixed solution was placed on a stirrer and stirred for 3 h to finally obtain a uniformly mixed solution. The uniformly mixed solution was subjected to a spray drying experiment, and the inlet temperature was set to 180°C, the outlet temperature was set to 80°C, and the sample feed rate was controlled. After the spray drying was completed, the precursor material obtained in the sample tank was collected.

[0064] The silicon-carbon precursor was placed in a porcelain ark and transferred to the center of a single-temperature-zone tubular furnace for carbonization under an inert atmosphere. After the temperature was raised to 400 °C for pretreatment for 2 h, the temperature was further raised to 950 °C and kept for 2 h. After cooling with the furnace, the samples were collected to obtain a silicon-carbon composite material, recorded as SI@EG@PF-1.

[0065] The above-mentioned SI@EG@PF-1 material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 h; the slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 min, and then transferred to an 80 °C vacuum drying oven for drying for 12 h. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using a blue electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 2 As shown, the battery is at 100mA g -1 At the current density, the discharge capacity is 1855.2 mAh g -1 , the charge capacity is 1635.5 mAh g -1 , the first efficiency is 88.2%, at 1 A g -1 At the current density, the capacity retention rate was 89.85% after 50 charge and discharge cycles. Example 2

[0066] 4 g of nano-silicon powder (80 nm) was dispersed in 150 mL of deionized water to obtain dispersion 1, and the dispersion was ultrasonically dispersed for 1 h. 3.2 g of graphene was dispersed in 100 mL of deionized water to obtain dispersion 2, and then stirred. 1.44 g of glucose, 0.72 g of cmc and 4.0 g of water-soluble phenolic resin (solid content of 70%) were dissolved in 150 mL of deionized water and stirred to obtain solution 3. After the above dispersion 2 and solution 3 were poured into dispersion 1, the mixed solution was placed on a stirrer and stirred for 3 h to finally obtain a uniformly mixed solution. The uniformly mixed solution was subjected to a spray drying experiment, and the inlet temperature was set to 180°C, the outlet temperature was set to 80°C, and the sample feed rate was controlled. After the spray drying was completed, the precursor material obtained in the sample tank was collected.

[0067] The silicon-carbon precursor was placed in a porcelain ark and transferred to the center of a single-temperature-zone tubular furnace for carbonization under an inert atmosphere. After the temperature was raised to 400 °C for pretreatment for 2 h, the temperature was further raised to 950 °C and kept for 2 h. After cooling with the furnace, the samples were collected to obtain a silicon-carbon composite material, recorded as SI@EG@PF-2.

[0068] The above-mentioned SI@EG@PF-2 material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 h; the slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 min, and then transferred to an 80 °C vacuum drying oven for drying for 12 h. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using the Blue Electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 3 As shown, the battery is at 100mA g -1 At the current density, the discharge capacity is 1949.3 mAh g -1 , the charge capacity is 1683.7 mAh g -1 The first efficiency is 86.4% at 1 A g -1 At the current density, the capacity retention rate was 89.87% after 50 charge and discharge cycles. Example 3

[0069] (1) 4 g of nano-silicon powder (80 nm) was dispersed in 150 mL of deionized water to obtain dispersion 1, and the dispersion was ultrasonically dispersed for 1 h. 3.2 g of graphene was dispersed in 100 mL of deionized water to obtain dispersion 2, and the dispersion was stirred. 1.44 g of glucose, 0.72 g of cmc and 4.55 g of water-soluble phenolic resin (solid content of 70%) were dissolved in 150 mL of deionized water and stirred to obtain solution 3. After the above dispersion 2 and solution 3 were poured into dispersion 1, the mixed solution was placed on a stirrer and stirred for 3 h to finally obtain a uniformly mixed solution. (2) The obtained mixed solution was subjected to a spray drying experiment, and the inlet temperature was set to 180°C and the outlet temperature was set to 80°C. The sample feed rate was controlled well. After the spray drying was completed, the precursor material obtained in the sample tank was collected.

[0070] (3) The silicon-carbon precursor was placed in a porcelain ark and transferred to the center of a single-temperature-zone tubular furnace for carbonization under an inert atmosphere. The temperature was raised to 400 °C for pretreatment for 2 h, and then the temperature was further raised to 950 °C for 2 h. After cooling with the furnace, the samples were collected to obtain a silicon-carbon composite material, which was recorded as SI@EG@PF-3.

[0071] The above-mentioned SI@EG@PF-3 material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 h; the slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 min, and then transferred to an 80 °C vacuum drying oven for drying for 12 h. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using a blue electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 4 As shown, the battery is at 100mA g -1 At the current density, the discharge capacity is 2282.5 mAh g -1 , the charging capacity is 2001 mAh g -1 , the first efficiency is 87.7%, at 1 A g -1 At the current density, the capacity retention rate was 82.24% after 50 charge and discharge cycles. Example 4

[0072] 4 g of nano-silicon powder (80 nm) was dispersed in 150 mL of deionized water to obtain dispersion 1, and the dispersion was ultrasonically dispersed for 1 h. 3.2 g of graphene was dispersed in 100 mL of deionized water to obtain dispersion 2, and then stirred. 1.44 g of glucose, 0.72 g of cmc and 4 g of water-soluble phenolic resin (solid content of 70%) were dissolved in 150 mL of deionized water and stirred to obtain solution 3. After the above dispersion 2 and solution 3 were poured into dispersion 1, the mixed solution was placed on a stirrer and stirred for 3 h to finally obtain a uniformly mixed solution. The uniformly mixed solution was subjected to a spray drying experiment, the inlet temperature was set at 180°C, the outlet temperature was set at 80°C, the sample feed rate was controlled, and after the spray drying was completed, the primary particles obtained in the sample tank were collected.

[0073] The obtained primary particles were coated with asphalt. First, 120 mg of asphalt was weighed into a beaker, and the asphalt was dissolved in a tetrahydrofuran solution in a fume hood. After stirring for a certain period of time to completely dissolve the asphalt, 300 mg of the primary particles obtained after spray drying were added, and the stirring was continued at 650 rad / s for 1 hour at room temperature. Then, the solution was heated and stirred in an oil bath to evaporate to dryness to obtain a silicon-carbon precursor. The silicon-carbon precursor was placed in a porcelain ark and transferred to the center of a single-temperature-zone tubular furnace for carbonization under an inert atmosphere. After the temperature was raised to 400 °C for pretreatment for 2 h, the temperature was further raised to 950 °C and kept for 2 h. After cooling with the furnace, the samples were collected to obtain a silicon-carbon composite material, recorded as SI@EG@PF@C-1.

[0074] The above-mentioned SI@EG@PF@C-1 material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 hours; the slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 minutes, and then transferred to an 80 °C vacuum drying oven for drying for 12 hours. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using the Blue Electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 5 As shown, the battery is at 100mA g -1 At the current density, the discharge capacity is 1629.4 mAh g -1 , the charge capacity is 1433.1 mAh g -1 , the first efficiency is 88%, at 1 A g -1 At the current density, the capacity retention rate was 86.83% after 50 charge and discharge cycles. Example 5

[0075] 4 g of nano-silicon powder (80 nm) was dispersed in 150 mL of deionized water to obtain dispersion 1, and the dispersion was ultrasonically dispersed for 1 h. 3.2 g of graphene was dispersed in 100 mL of deionized water to obtain dispersion 2, and then stirred. 1.44 g of glucose, 0.72 g of cmc and 4 g of water-soluble phenolic resin (solid content of 70%) were dissolved in 150 mL of deionized water and stirred to obtain solution 3. After the above dispersion 2 and solution 3 were poured into dispersion 1, the mixed solution was placed on a stirrer and stirred for 3 h to finally obtain a uniformly mixed solution. The uniformly mixed solution was subjected to a spray drying experiment, the inlet temperature was set at 180°C, the outlet temperature was set at 80°C, the sample feed rate was controlled, and after the spray drying was completed, the primary particles obtained in the sample tank were collected.

[0076] The obtained primary particles were coated with asphalt. First, 180 mg of asphalt was weighed into a beaker, and the asphalt was dissolved in a tetrahydrofuran solution in a fume hood. After stirring for a certain period of time to completely dissolve the asphalt, 300 mg of the primary particles obtained after spray drying were added, and the mixture was stirred at 650 rad / s for 1 hour at room temperature. The solution was then heated and stirred in an oil bath to evaporate to dryness to obtain a silicon-carbon precursor. The silicon-carbon precursor was placed in a porcelain ark and transferred to the center of a single-temperature-zone tubular furnace for carbonization under an inert atmosphere. After the temperature was raised to 400 °C for pretreatment for 2 h, the temperature was further raised to 950 °C and kept for 2 h. After cooling with the furnace, the samples were collected to obtain a silicon-carbon composite material, recorded as SI@EG@PF@C-2.

[0077] The above-mentioned SI@EG@PF@C-2 material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 hours; the slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 minutes, and then transferred to an 80 °C vacuum drying oven for drying for 12 hours. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using the Blue Electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 6 As shown, the battery is at 100mA g -1At the current density, the discharge capacity is 1285 mAh g -1 , the charge capacity is 1100.8 mAh g -1 The first efficiency is 85.7% at 1 A g -1 The capacity retention rate after 50 charge and discharge cycles was 94.38%. -1 The discharge capacity is 1355.8 mAh g -1 , the charge capacity is 1150.6 mAh g -1 The initial efficiency is 84.9%, and the capacity retention rate is 87.8% after 100 charge and discharge cycles. Example 6

[0078] 4 g of nano-silicon powder (80 nm) was dispersed in 150 mL of deionized water to obtain dispersion 1, and the dispersion was ultrasonically dispersed for 1 h. 3.2 g of graphene was dispersed in 100 mL of deionized water to obtain dispersion 2, and then stirred. 1.44 g of glucose, 0.72 g of cmc and 4 g of water-soluble phenolic resin (solid content of 70%) were dissolved in 150 mL of deionized water and stirred to obtain solution 3. After the above dispersion 2 and solution 3 were poured into dispersion 1, the mixed solution was placed on a stirrer and stirred for 3 h to finally obtain a uniformly mixed solution. The uniformly mixed solution was subjected to a spray drying experiment, the inlet temperature was set at 180°C, the outlet temperature was set at 80°C, the sample feed rate was controlled, and after the spray drying was completed, the primary particles obtained in the sample tank were collected.

[0079] The obtained primary particles were coated with asphalt. First, 240 mg of asphalt was weighed into a beaker, and the asphalt was dissolved in a tetrahydrofuran solution in a fume hood. After stirring for a certain period of time to completely dissolve the asphalt, 300 mg of the primary particles obtained after spray drying were added, and the mixture was stirred at 650 rad / s for 1 h at room temperature. The solution was then heated and stirred in an oil bath to evaporate to dryness to obtain a silicon-carbon precursor. The silicon-carbon precursor was placed in a porcelain ark and transferred to the center of a single-temperature-zone tubular furnace for carbonization under an inert atmosphere. After the temperature was raised to 400 °C for pretreatment for 2 h, the temperature was further raised to 950 °C and kept for 2 h. After cooling with the furnace, the samples were collected to obtain a silicon-carbon composite material, recorded as SI@EG@PF@C-3.

[0080] The above-mentioned SI@EG@PF@C-3 material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 hours; the slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 minutes, and then transferred to an 80 °C vacuum drying oven for drying for 12 hours. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using a blue electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 7 As shown, the battery is at 100mA g -1 At the current density, the discharge capacity is 1333.2 mAh g -1 , the charge capacity is 1153.1 mAh g -1 , the first efficiency is 86.5%, at 1 A g -1 At the current density, the capacity retention rate was 87.54% after 50 charge and discharge cycles. Comparative Example 1

[0081] The uncoated nano-silicon material is directly used as the negative electrode material of lithium-ion batteries.

[0082] Si nano-silicon material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 h. The slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 min, and then transferred to an 80 °C vacuum drying oven for drying for 12 h. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using a blue electric system, with an initial current density of 100 mA g -1 Activated for 5 cycles, then heated to 1 A g -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Figure 8 As shown, the battery is at 100 mA g -1At the current density, the discharge capacity is 3706.5 mAh g -1 , the charge capacity is 2902.6 mAh g -1 , at 1 A g -1 At the current density, the capacity decayed to less than 50 mAh g after 50 charge and discharge cycles. -1 . Comparative Example 2

[0083] The commercially available silicon-carbon negative electrode material A was directly used as the negative electrode material for lithium-ion batteries.

[0084] Si@C commercial silicon carbon A material, super P, and cmc were weighed and ground in a mass ratio of 8:1:1, and deionized water was added to form a uniformly mixed slurry, which was mechanically stirred for 5 h. The slurry was evenly coated on the copper foil using an automatic coating machine, pre-dried for 30 min, and then transferred to an 80 °C vacuum drying oven for drying for 12 h. Then it was cut into 12 mm pole pieces. The pole pieces were assembled into 2032 button half-cells in an argon glove box, using lithium foil as the counter electrode and 1 mol / L LiPF6 (EC / DEC / EMC 1:1:1) as the electrolyte. The amount of electrolyte added to each battery was 60 μL, and a Celgard diaphragm (diameter 19 mm) was used. The battery charge and discharge cycle was tested using a blue electric system, with an initial current density of 100 mA g -1 Activate for 5 cycles, then use 1 Ag -1 Long-term cycle test was carried out at current density and voltage range of 0.01-2 V. The test results are as follows Fig. 9 As shown, the battery is at 200 mA g -1 At the current density, the discharge capacity is 1060.3 mAh g -1 , the charge capacity is 878.6 mAh g -1 After 100 charge and discharge cycles, the capacity retention rate is 78.66%. Performance Testing

[0085] The rate performance of the batteries assembled in Examples 1-6 and Comparative Examples 1-2 was tested at different current densities. The test results are as follows: Fig.11 As shown. Fig.11It can be seen that the performance of the battery prepared by the silicon-carbon negative electrode material of Example 1-6 is better than that of the battery prepared by the Si negative electrode material of Comparative Example 1 and the Si@C negative electrode material of Comparative Example 2. Furthermore, since the silicon-carbon negative electrode material prepared in Example 1-3 is coated only once, the silicon-carbon negative electrode material has a high proportion of silicon, so the specific capacity of the electrode material is high, but during the cycle process, the capacity decay rate of the battery prepared in Example 1-3 is faster, and the silicon-carbon negative electrode material prepared in Example 4-6 has a micro-nano spherical structure coated with a double carbon layer due to the secondary coating, which reduces the proportion of silicon in the material and the specific capacity, but the capacity decay of the battery is slower during the cycle, and the capacity retention rate of the battery is higher when changing different rates.

[0086] The SI@EG@PF-2 material of Example 2 and the SI@EG@PF@C-2 material of Example 5 were subjected to BET test. The test results are as follows: Fig.12 , Fig.13 As shown. The specific surface area of ​​the SI@EG@PF@C-2 material after secondary carbon coating is significantly smaller than that of the SI@EG@PF-2 material after only one carbon coating. This shows that the asphalt carbon on the outside can modify the structural defects of the amorphous carbon inside, making the material's specific surface area lower and the structure more compact, thereby forming a stable SEI film during the electrochemical process, improving the thermal stability and electrical conductivity of the material, and improving the performance of the prepared silicon-carbon negative electrode material in all aspects.

[0087] The beneficial effects of the double carbon layer coated silicon carbon negative electrode material and the preparation method thereof provided in the present application include but are not limited to the following: The silicon-carbon material prepared by the present invention has a loose and porous middle carbon layer and a high-density outer carbon layer, forming a composite micron particle structure of double-layer carbon-coated silicon particles. The porous structure of the inner carbon layer can better absorb the volume expansion of the silicon particles during the charging and discharging process, reduce internal stress, and thus improve the cyclic stability of the material. The outer carbon layer structure obtained by carbonizing asphalt can fill the larger pores formed by a single coating, further modifying structural defects, making the material structure denser, and helping to form a stable SEI film.

[0088] The double carbon layer silicon-carbon negative electrode material prepared by the present invention has a higher specific capacity, good cycle performance, high capacity retention rate, simple preparation method, simple raw material source, low cost, and is suitable for industrial production.

[0089] The silicon-carbon negative electrode material prepared by the present invention has a high initial coulombic efficiency and capacity retention rate, and shows superior performance in terms of initial capacity, reversible capacity and residual capacity retention rate after cycling compared with a commercial silicon-carbon negative electrode material on the market. Therefore, it has a wide range of application prospects in the field of lithium-ion batteries and can significantly improve the energy density and charge and discharge performance of the battery.

[0090] In summary, after reading the contents of this application, those skilled in the art will appreciate that the aforementioned application contents may be presented only in an exemplary manner and may not be restrictive. Although not explicitly stated herein, those skilled in the art will appreciate that this application is intended to encompass various reasonable changes, improvements and modifications to the embodiments. These changes, improvements and modifications are within the spirit and scope of the exemplary embodiments of this application.

Claims

1. A method for preparing a double carbon layer coated silicon-carbon negative electrode material, characterized in that: include: (1) Solution preparation: dispersing the nano-silicon material in water, adding the amorphous carbon precursor material to dissolve and mix and disperse to obtain a precursor solution, wherein the mass ratio of the nano-silicon material to the amorphous carbon precursor material is 1:(0.5-4); (2) spray drying: spray drying the precursor solution to obtain primary particles; (3) Liquid phase coating: dissolving the primary particles and asphalt in a solvent, mixing and stirring, and heating and evaporating to obtain a silicon-carbon precursor coated with a double carbon layer; (4) Carbonization: The silicon-carbon precursor is heated to 300-400°C in an inert atmosphere for low-temperature carbonization treatment for 1-2 hours, and then heated to 800-100°C for high-temperature carbonization and heat preservation for 1-2 hours. After cooling, the double carbon layer-coated silicon-carbon negative electrode material is obtained.

2. The preparation method according to claim 1, characterized in that: The amorphous carbon precursor in step (1) includes at least one of glucose, sucrose, water-soluble phenolic resin, starch and asphalt.

3. The preparation method according to claim 2, characterized in that: In the step (1), the nano silicon material is dispersed by ultrasound, the ultrasonic dispersion time is 0.5-3h, and the particle size of the nano silicon material is 50 nm-500 nm.

4. The preparation method according to claim 3, characterized in that: In the step (1), the precursor solution also includes a conductive agent, which includes at least one of exfoliated graphene, graphene oxide, conductive graphite, carbon black, carbon nanotubes, and carbon fibers, and the mass ratio of the nano-silicon material to the conductive agent is 1:(0.8-2).

5. The preparation method according to claim 4, characterized in that: In the step (1), the precursor solution further comprises a binder, and the binder comprises at least one of sodium carboxymethyl cellulose, polyacrylic acid, and polyvinyl pyrrolidone, and the mass ratio of the nano-silicon material to the binder is 1:(0.01-0.2).

6. The preparation method according to claim 5, characterized in that: In the step (2), the air inlet temperature in the spray drying experiment is 140-220°C, and the air outlet temperature is 60-90°C.

7. The preparation method according to claim 6, characterized in that: In the step (3), the asphalt includes at least one of natural asphalt, coal tar asphalt, petroleum asphalt or modified asphalt, the mixing time is 0.5-3 h, and the stirring speed is 500-650 rpm.

8. The method for preparing a double carbon layer coated silicon-carbon negative electrode material according to claim 7, characterized in that: In the step (4), the silicon-carbon precursor is heated at a heating rate of 5-10° C. / min in an argon atmosphere.

9. A double carbon layer coated silicon-carbon negative electrode material, characterized in that: The double carbon layer coated silicon-carbon negative electrode material is prepared by the method according to any one of claims 1 to 8.

10. A lithium-ion battery comprising the double carbon layer-coated silicon-carbon negative electrode material according to claim 9.